Use the drop-down menus to choose steps in order to correctly solve
1 + 2b – 13 = 12 – 4b – 2b
2b = 24 – 4b – 2b
Lost your password? Please enter your email address. You will receive a link and will create a new password via email.
Please briefly explain why you feel this question should be reported.
Please briefly explain why you feel this answer should be reported.
Please briefly explain why you feel this user should be reported.
To solve the equation step by step, let’s start with the given equation:
1 + 2b – 13 = 12 – 4b – 2b
First, simplify both sides:
1. Combine like terms on the left:
– 1 – 13 = -12, so it becomes:
-12 + 2b = 12 – 6b
2. Now, move all the terms involving “b” to one side and constants to the other side. Add 6b to both sides:
-12 + 2b + 6b = 12
-12 + 8b = 12
3. Next, isolate the term with “b” by adding 12 to both sides:
8b = 12 + 12
8b = 24
4. Finally, divide by 8 to solve for “b”:
b = 24 / 8
b = 3
So, the solution is b = 3. This entire process shows us how to manipulate the equation by combining like terms and isolating the variable step by step. If you need further clarification or help, feel free to check our extended services page!